RICE BRAN OIL EXTRACTION TECHNOLOGY UPAYA PENINGKATAN NILAI TAMBAH BEKATUL KELOMPOK TANI DESA KALIBARU - megandhi wardhana; Bagus Setyawan; Adi Pratama Putra (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The majority of rice farmers in Kalibaru Wetan Village only use rice bran conventionally, namely as a mixture of animal feed only. This is caused by the lack of community knowledge to process rice bran into high-value products, so that the partner problems that are our priority as the PKM team are: 1). The rice farmer group in Kalibaru Wetan Village has not maximized the results of milling rice bran into high-value products, 2) Traditional product management model, and 3) Local product marketing. Rice farmers in Kalibaru Wetan Village sell cheaply milled rice bran to middlemen or collectors for around 500-1000 per kg. This PKM activity partner is one of the farmer groups in Kalibaru Wetan Village which is chaired by Abdullah. The purpose of this service is so that rice farmers have knowledge of making rice bran oil, packaging rice bran oil and selling rice bran oil. The method implemented is by providing counseling and mentoring to male and female farmers in stages so that the monitoring and evaluation process is carried out more optimally on an ongoing basis. The results obtained are that the rice farmers of Kalibaru Wetan Village succeeded in making rice bran oil and were successful in designing, packaging products and selling products. It can be concluded that rice farmers can use the machine easily and increase their income.